Red blood cell alloimmunization among transfusion-dependent thalassemia major patients in Northeastern Iran - Leila Mobasheri; Tayyebeh Chahkandi; Amir Talebpour; Gholamreza Anani Sarab (Asian Journal of Transfusion Science)
BACKGROUND: Thalassemia is one of the most common congenital hemoglobinopathies globally. Regular red blood cell (RBC) transfusion is of paramount importance in the treatment of thalassemia patients. However, this practice increases the risk of alloimmunization. This study was performed to determine the prevalence of RBC antibodies among multiple-transfused thalassemic patients in southern Khorasan, the eastern side of Iran. METHODS: For the purpose of screening unexpected antibodies, blood samples of 68 β-thalassemia major patients were investigated. After determining positive cases through screening phase, the process of antibody identification was carried out using reagent cells. RESULTS: The overall rate of alloimmunization was 2.9%, and the most frequent clinically important alloantibodies were anti-Kell and anti-Rh systems. Anti-K was detected in one of the patients. Furthermore, the simultaneous occurrence of anti-E and anti-C was seen in another study subject. CONCLUSION: A number of factors might have contributed to the low alloimmunization rate detected in this study, including the homogeneity of the population in South Khorasan, well-matched donors for those patients, first transfusion at an early age, and the use of leukodepleted blood.